Stem cell microenvironments and beyond - Birbrair, Alexander (Springer, 2017)
"This book discusses the main stem cell niches under distinct pathophysiological conditions. The role of tissue microenvironments in stem cell regulation, as well as modern methodologies and new techniques for the identification and characterization of stem cell niches, are discussed by leading experts in the field. Chapters describe the major components of various stem cell microenvironments, such as cellular components, soluble factors, cell-cell interactions, extra-cellular matrix proteins, and physical forces. Stem Cell Microenvironments and Beyond is part of the highly successful Advances in Experimental Medicine and Biology series. It is essential reading for graduate students and researchers in the field of stem cells or cell biology as well as clinicians"--Publisher's description.
Keywords: Stem cells -- Research.; elektronické knihy; electronic books